Community identity and collective efficacy: A social cure for traumatic stress in post‐earthquake Nepal. (13th October 2017) - Muldoon, Orla T.; Acharya, Khagendra; Jay, Sarah; Adhikari, Kamal; Pettigrew, Judith; Lowe, Robert D.
Abstract: Post‐Traumatic Stress Disorder (PTSD) was initially conceptualized as a psychopathology that arose as a consequence of war time experiences. More recently, available evidence has demonstrated that post‐traumatic stress (PTS) as a consequence of war is buffered by social identity processes. In such contexts, identity resources are arguably more readily accessible given the integral relationship between social identities and intergroup violence. There is no evidence as yet to suggest that social identity processes may act to reduce PTS responses to naturally occurring disasters such as earthquakes and even less data pertaining to non‐Western contexts where the impact of such disasters tends to be particularly catastrophic. This article reports on a study undertaken in earthquake‐affected regions in Nepal devastated by the April 2015 quake and its major aftershock a month later. Participants (n=399) completed measures of their earthquake experience, Post‐Traumatic Stress and Post Traumatic growth (PTG), as well as measures of community identification and collective efficacy. In total 399 people completed the measures approximately six months after the quakes. Results of the study indicated that consistent with tenets of the social identity framework, ethnic and gender group memberships impacted on reported experiences during the earthquake. Reported experience during the quakes and ethnic group membership were both related to increased symptoms of PTS. Ethnicity was also linked to the proportion of respondents reporting clinical levels of PTSD symptoms. The relationship between earthquake experience and PTG was mediated by community identification and collective efficacy. Earthquake experience also had an indirect effect on PTS through collective efficacy. Implications of these findings for those working with traumatized groups are discussed.